Human Resources As A Factor Supporting The Success Of The Cooperation Sister City Semarang-Brisbane - Albert, Albert; Santoso, Thomas Budi; Irmawati, B (Universitas Semarang, 2018)
Sister city collaboration is an activity carried out based on cooperation agreements between city governments in Indonesia and city governments abroad to mutually improve relations of friendship and understanding between the two countries. The Semarang Government on 11 January 1993 signed the first Sister City Memorandum of Understanding (MoU) with Lord Mayor Brisbane, Queensland, Australia. Unfortunately, this MoU of cooperation was halted in 2005, and although the MoU was still ongoing the implementation of the program activities stopped in 1997. The results of previous studies showed several factors as factors supporting the success of sister city cooperation. One of the supporting factors is the factor of human resources (HR). The purpose of this study is to identify aspects of the human resource factor that can support the success of the Semarang-Brisbane sister city activity.Primary data collection in this study was in the form of a questionnaire and interview to eight respondents from various backgrounds. The analysis in this study was carried out using descriptive analysis to describe the opinions of respondents about human resource factors that support the success of Semarang-Brisbane sister city.The results of the study show that the important HR competency factors are those who have an understanding of the culture and language of the partner countries. Whereas according to its importance the competence of human resources is mastering English or other relevant languages, understanding partner countries, experts in the field of international agreements and mastering foreign policy.